CONTEMPORARY ISSUES OF THE RESTITUTION OF PROPERTY IN SERBIA - Veselinov, Jelena (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
The process of restitution, in its basic concept, has to set equally two objectives: a) elimination of the injustices, i.e. restitution of property to former owners who were stripped from the property during state intervention; b) creating conditions for market-oriented economic subjects and conditions for achieving greater economical stability. Without that, restitution will have limited reach. Serbian Law on Property Restitution and Compensation was passed only just in 2011, when the process of transformation of ownership was in the act for more than two decades. If relations of property are affected during the change of fundamental principles in organizing the society, the principle of fairness must require that all subjects, if it’s possible, be in the same legal position. However, when it comes to restitution, adoption and implementation of regulations make indirect discrimination. This paper deals only with current restitution issues that refer to the violation of basic legal principles: The differences in the legal status of persons who were deprived of their property; The differences in the possibilities of exercising the rights of persons whose deprived property is returned on the basis of the general law and the law on property restitution to churches and religious communities; Different degree of legal certainty for the persons whose property is returned in kind and for persons that are given cash and securities for reimbursement. Problems in the implementation of the law which, under the applicable legislation, practically and theoretically, cannot be resolved, were presented in the paper in order to point out the serious shortcomings and contradictions in the text of the Law and to point out the need for amendments.